Penyiapan Siswa Menghadapi Asesmen Kompetensi Minimum - Ani Rusilowati; Masrukan Masrukan; R. Susanti; Triastuti Sulistyaningsih; Tri Sri NoorAsih; Heru Setyanto (BERDAYA Indonesian Journal of Community Empowerment, 2024)
Elementary school teachers in Gunungpati District, Semarang, still experience difficulties in: (1) implementing learning that can prepare students to face the minimum competency assessment (AKM), (2) compiling instruments that can be used to train students to face AKM, namely literacy and numeracy. Therefore, it is necessary to carry out training activities for teachers in the KKG, in order to prepare them to familiarize their students with knowing and taking literacy and numeracy tests. The aim of this service activity is to provide training for teachers through KKG activities with a facilitation-based Action Learning model. The specific aim is to assist elementary school teachers in improving their pedagogical competence in the areas of learning and evaluation. The problem solving method that has been agreed upon by partners is the implementation of programmed training. The solution method design refers to the facilitation-based Action Learning model. Action learning is defined as a process in which a group of people come together regularly, help each other to learn, and share experiences. This training requires a tutor who acts as a facilitator, and continues with the mentoring phase. Before carrying out the training, a Focus Group Discussion (FGD) was held with several elementary school principals and the head of the Dewi Kunthi KKG, Gunungpati District, Semarang. The results of the FGD are used to design training scenarios for each activity and training materials. The success of the training was marked by the increasing ability of teachers in designing science and science lessons and preparing AKM questions, namely literacy and numeracy.